Factors Influencing Occupational Therapists' Decision to Supervise Fieldwork Students. Issue 3 (3rd July 2017) - Varland, Joscelyn; Cardell, Elizabeth; Koski, Jeanette; McFadden, Molly
ABSTRACT: The purpose of this study was to identify factors that influence the decision to supervise a Level II occupational therapy fieldwork student. A survey was sent to occupational therapists identified from licensure boards and alumni rosters, including those who have and have not supervised students ( n = 548). The results identified both positive and negative influences along with predictive factors of supervising a student. While positive factors included continuing education units, education on fieldwork expectations, their own fieldwork experiences, shared supervision, and access to educational resources, negative influences consisted of: job responsibilities, caseload, productivity standards, working part-time, and fear of failing a student. The discussion focuses on how to address the needs of the clinician and facilitate fieldwork placement.